Agresividad y su influencia en el rendimiento académico de un adolescente de 15 años - Mosquera Cerezo, Fabia Bolivia (2020)
Next, we study the case of a 15-year-old teenager, who according to his school history presents aggressive behavior, insults his classmates, aggravates them, and also shows himself challenging in classes with the teachers, which has caused them to decrease Your qualifications First of all, in order to obtain results, an investigation was carried out on the behaviors that the adolescent presents in the school and it was determined that he has aggressive behaviors and a low academic performance, to assess the origin of such aggressiveness, a questionnaire was applied to analyze if his aggressiveness is reactive or proactive, that is, to know if it is caused by stimuli or originates internally; Four interviews were also carried out to know the patient's perspective and to establish connections with the possible causes. These types of cases should be referential for both parents and psychology professionals that, in view of such behavioral problems, this problem must be addressed and addressed before it generates worse consequences. As for the treatment that the patient deserves, a series of therapies with a cognitive behavioral approach must be carried out to work on the feelings, safety and self-esteem of the boy, in order to improve aspects such as interpersonal relationships, academic performance and his general perspective of surrounding environment.